Quality evaluation and discrimination of flavouring process of garlic-flavoured vegetable oils - Gonzalez, Roxana Elizabeth; Vidoni, María Natalia; Locatelli, Daniela Ana; Camargo, Alejandra Beatriz (2018)
In this study, the effects of two garlic-flavouring processes on quality parameters and the organosulphur compound profile were investigated. The results showed that the addition of fresh garlic increased acidity and peroxide values in all flavoured vegetable oils. Mono-, di-, and trisulphides were mainly present in aromatised oils, while allicin, ajoene, and vinyldithiins were found in macerated oils. Analyses of the principal components demonstrate that flavoured oils could be discriminated according to the flavouring processes. The experiments carried out in this study would allow one to predict the results of a flavouring procedure on an unknown sample and, consequently, its potential beneficial effects.